Cultural influences on mental health symptoms in a primary care sample of Latinx patients. (April 2018) - Escovar, Emily L.; Craske, Michelle; Roy-Byrne, Peter; Stein, Murray B.; Sullivan, Greer; Sherbourne, Cathy D.; Bystritsky, Alexander; Chavira, Denise A.
Highlights: Proportions of specific anxiety disorders are similar between Latinx and non-Latinx Whites in a primary care sample. Latinx expressed greater levels of somatization and physical functional impairment than non-Latinx Whites. Perceived discrimination may be an important factor to consider when examining risk for greater symptom burden among Latinx with anxiety. Abstract: The present study examines how both between group (i.e., ethnic group membership) and within group cultural factors (i.e., nativity status, age of immigration, and perceived discrimination) may contribute to anxiety and related symptoms in Latinx with anxiety disorders. Baseline data were examined from patients who participated in one of the largest intervention studies for adults with anxiety disorders in primary care settings; 196 Latinx and 568 NLW (non-Latinx White) patients participated. Proportions of anxiety disorders were similar between Latinx and NLWs; however, Latinx, on average, had a greater number of anxiety disorders than NLWs. Levels of anxiety and depression symptom severity, anxiety sensitivity, and mental functional impairment were similar between the ethnic groups. Latinx expressed greater somatization and physical functional impairment than NLWs. Among Latinx, perceived discrimination, but not other cultural variables, was predictive of mental health symptoms while controlling for age, gender, education, and poverty. Overall, these findings suggest more similarities than differences in types and levels of anxiety and anxiety-related impairment, with some important exceptions, including greater levels of somatization and physical functional impairment among Latinx patients. Further, perceived discrimination may be an important factor to consider when examining risk for greater symptom burden among Latinx with anxiety.